A robot hand with free-rotating grips for switching three different grasping modes. (17th September 2022) - Seki, Masashi; Wada, Kazuyoshi; Teraguchi, Tomoya; Tomizawa, Tetsuo
ABSTRACT: The automation of the display and disposal of products on shelves has attracted widespread attention because it is the most time-consuming task in convenience store operations. However, robots find it difficult to perform store operations because products vary in shapes and sizes and must be displayed in specific positions on narrow shelves. In this study, we developed a robot hand that can grasp various products and easily change its posture. The hand has two free rotating grips that allows the robot to change position between the following three grasping modes: (i) grasp mode: prevents the free rotation of an object, (ii) rotation mode: changes the posture of the object due to its weight, and (iii) scoop mode: allows the robot to grasp a flat object. A performance evaluation experiment was conducted using the robot hand. Subsequently, three results were obtained. First, the robot hand successfully grabbed a cork block, a rice ball, and a sandwich in the grasp and rotation mode, and the gripper behavior changed depending on the grasping mode. Second, the robot hand successfully grasped a lunch box in the scoop mode. Third, the robot hand switched from the grasp to the rotation mode while grasping the object. These results indicate that the hand can change its posture owing to gravity at any time. GRAPHICAL ABSTRACT: UF0001